Analysis of foreign physical activity recommendations and guidelines for schools - Jan Pavelka; Erik Sigmund; Zdeněk Hamřík; Michal Kalman (Palacký University Olomouc, 2014)
Background:An adequate level of physical activity is an important part of children's lifestyle. The school environment plays a significant role in the area of interventions and strategies aiming to increase the level of physical activity in children. Objectives: The aim of this study is to analyse foreign recommendations leading to an increased level of physical activity in children and young people in Czech schools. Methods: A systematic search of studies published between 1988 and 2012 in the English language was completed in library databases Medline, Sport Discus, ProQuest, PsychInfo, ERIC, Wiley InterScience using the following keywords: physical activity, guidelines, recommendations, school and youth. The studies were then classified based on abstract and full-text analyses. Using a content analysis the expert team formulated the final recommendations to increase the level of physical activity for schools in the Czech Republic (CR). Results: Out of the total number of 91 identified foreign studies, 25 met the predetermined criteria and were used as a basis for formulating the recommendations. These foreign studies included 15 papers published in USA, two in Australia, two in Great Britain, two in Canada, one in the European Union, one in New Zealand and one international paper (an international consensus of experts from 34 countries). Based on the interpretation of the evidence, its justification and final consensus of the expert team, the basic areas for the recommendations to increase the level of physical activity in schools in the CR were identified. Conclusions: An analysis of foreign recommendations to increase the level of physical activity designed for schools and school facilities is one of the possible methods of formulating domestic recommendations. This recommendation could contribute to deeper understanding of the issue of the deteriorating lifestyle of school-aged children in the CR and reflects the efforts for improvement.